2011
DOI: 10.1007/s12639-011-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Serodetection of Ehrlichia canis infection in dogs from Ludhiana district of Punjab, India

Abstract: Dot-ELISA (enzyme-linked immunosorbent assay) Immunocomb(®) assay was conducted to detect the presence of antibodies against Ehrlichia canis in blood samples of 60 privately owned dogs suspected to be infected with E. canis from the Small Animal Clinics, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, Punjab (India). Antibodies reactive to E. canis were detected in plasma in 48 samples out of 60 samples by Immunocomb(®) Dot-ELISA. Out of these 39.58% samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…E. canis is more prevalent in tropical and subtropical areas in India, Asia, Central and South America and Africa (SINGLA et al, 2011;BABA et al, 2012;RODRIGUEZ-VIVAS et al, 2005;AGUIAR et al, 2007a;MATJILA et al, 2008). In South America, it has been reported in Brazil (VIEIRA et al, 2011), Venezuela (UNVER et al, 2001, Chile (LÓPEZ et al, 2012) and Peru (VINASCO et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…E. canis is more prevalent in tropical and subtropical areas in India, Asia, Central and South America and Africa (SINGLA et al, 2011;BABA et al, 2012;RODRIGUEZ-VIVAS et al, 2005;AGUIAR et al, 2007a;MATJILA et al, 2008). In South America, it has been reported in Brazil (VIEIRA et al, 2011), Venezuela (UNVER et al, 2001, Chile (LÓPEZ et al, 2012) and Peru (VINASCO et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…B. gibsoni (Table 1). The limitations of microscopy in detecting E. canis morulae has also been reported by prior studies (Mylonakis et al, 2004;Singla et al, 2011;Abd Rani et al, 2011) and therefore make it a less sensitive technique for confirmatory diagnosis of canine ehrlichiosis. Moreover, sensitivity of E. canis detection by microscopy is low due to the fact that in chronic cases number of infected cells in peripheral circulation is very less to be detected by microscopic examination.…”
Section: Discussionmentioning
confidence: 83%
“…Prevalence studies of CME from Northern India were mainly concentrated from Ludhiana city in Punjab over the last few years in pet dogs and non-descript local dogs that were bought to the clinic. Singla et al (2011) reported a high seroprevalence of 61% in pet dogs when tested by commercial serological kit. The same group in their molecular studies through nested PCR in 2016 in the same city detected meagre 0.39% prevalence of E. canis DNA in pet dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strays may also include the quasi-owned animals that are cared for or considered to belong to the "neighbourhood" (Childs et al, 1998). Stray dogs pose several public health risks and concerns to humans, such as rabies (Reyers et al, 1998;Crosby, 2011), toxocariasis and ancylostomiasis (Croese et al, 1994;Prociv and Croese 1996;Singla et al, 2005;Chen et al, 2012), hydatidosis (Buishi et al, 2006), acquired epilepsy due to neurocysticercosis (Sharma et al, 2011), leishmaniasis, borreliosis, bartonellosis, ehrlichiosis, rickettsiosis (Day, 2011;Singla et al, 2011), and schistosomiasis (Hackett and Lappin, 2003).…”
Section: Introductionmentioning
confidence: 99%